Parikrma Humanity Foundation - Sharma, Rajeev (Of Indian Institute of Management, Ahmedabad) (London : Indian Institute of Management, Ahmedabad, 2018)
The Parikrma Humanity Foundation runs four schools for children who are first generation school goers. All children learn English and are provided three meals every day in school. Over the years the school has developed pedagogies, processes and structure of organizing the school so that children learn well, and teachers grow and contribute happily. The foundation also has an active community engagement programme to help reduce instances of domestic violence and aide in generating income. The case also demonstrates that children who have no support from their families can also learn and excel in education and in a co-curricular field if proper support and encouragement is provided in schools.
Originally Published InSharma, R. (2018). Parikrma Humanity Foundation. RJMC0044. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Parikrma Humanity Foundation; Children with social disabilities -- Education -- India -- Case studies